Time-lag of record inputs to the international nuclear information system bibliographic database. (1st January 2011) - Prakasan, E.R.; Bhaskar, Nita; Bhanumurthy, K.
This paper discusses the timeliness in inputting bibliographical records to international databases with a case study of the international nuclear information system bibliographic database from the inception (1970) to the year 2008. The authors have attempted to calculate the overall and average inputting time-lag of the database. The time-lags of inputting countries and international organisations are analysed separately. The study also tries to identify the nature of inputs that are responsible for this delayed response.